Actual provision as an alternative criterion to improve the efficiency of payments for ecosystem services for C sequestration in semiarid vineyards. (May 2016) - Galati, Antonino; Crescimanno, Maria; Gristina, Luciano; Keesstra, Saskia; Novara, Agata
Abstract: The aim of this paper is to evaluate the efficiency of the PES scheme actually used in the Sicilian rural development program, based on an egalitarian criterion, and proposing an alternative scheme in order to guarantee a greater equity and fairness of premium distribution in relation to soil carbon (C) sequestration potential. We, first, assessed the ecosystem services (ES) provided by agri-environmental measures (AEM) in terms of SOC stock increase in Sicilian vineyards. Based on these data we evaluated the efficiency of agro-environmental payments according to an egalitarian criterion and simulated the effects of the actual provision criterion adoption. Results showed that the adoption of an egalitarian criterion generates an inequitable distribution of agri-environmental payments, which could potentially be mitigated by a scheme such as actual provision. The latter, indeed, leads to a greater efficiency in the distribution of financial resources among land users and offers a higher premium to land users that, by adopting an agro-environmental practice, contribute to increase soil C sequestration. Highlights: We compare two alternative criteria for distribution of PES. The ecosystem services, in terms of carbon budget, were estimated under two different soil management. We demonstrate, using empirical data, the efficiency of the actual provision criterion.